A framework for scaling sustainable land management options. (30th July 2018) - Thomas, Richard; Reed, Mark; Clifton, Kathyrn; Appadurai, Nathan; Mills, Anthony; Zucca, Claudio; Kodsi, Elie; Sircely, Jason; Haddad, Fida; Hagen, Christopher; Mapedza, Everisto; Woldearegay, Kifle; et al.
Abstract: Improvements in land use and management are needed at a global scale to tackle interconnected global challenges of population growth, poverty, migration, climate change, biodiversity loss, and degrading land and water resources. There are hundreds of technical options for improving the sustainability of land management and preventing or reversing degradation, but there are many sociocultural, institutional, economic, and policy barriers hindering their adoption at large scale. To tackle this challenge, the Dryland Systems Program of the Consultative Group for International Agricultural Research and the UN Convention to Combat Desertification convened an expert group to consider barriers and incentives to scaling technologies, processes, policies, or institutional arrangements. The group reviewed existing frameworks for scaling sustainable land management (SLM) interventions across a range of contexts and identified eight critical actions for success: (a) plan iteratively; (b) consistently fund; (c) select SLM options for scaling based on best available evidence; (d) identify and engage with stakeholders at all scales; (e) build capacity for scaling; (f) foster institutional leadership and policy change to support scaling; (g) achieve early benefits and incentives for as many stakeholders as possible; and (h) monitor, evaluate, and communicate. Incentives for scaling were identified for the private sector, farmers and their communities, and policy makers. Based on these findings, a new action framework for scaling is presented that analyses the contexts where specific SLM interventions can be scaled, so that SLM options can be screened and adapted to these contexts, piloted and disseminated. The framework can help countries achieve land degradation neutrality.